Antioxidant compounds, antioxidant activities, and mineral contents among underutilized vegetables - Md. Amirul Alam; Tuan Aini T. Ngah; Gazi Md Mohsin; M Saleh (Taylor & Francis, 2020)
Natural sources may be a method to introduce antioxidants in the human diet. Portulaca oleracea L., Peperomia pellucida L., and Trianthema portulacastrum L are underutilized leafy vegetables. The plants may be sources for total phenolic (TPC), total flavonoid (TFC), total carotenoid (TCC), and β-carotene but information is lacking. Antioxidant activity, ferric reducing antioxidant power (FRAP), and 1,1-diphenyl-2-picrylhydrazyl (DPPH), and macro- and microminerals contents were investigated in P. oleracea, P. pellucida and T. portulacastrum. Trianthema portulacastrum had the highest TPC (1.34 ± 0.13 mg∙g−1), TFC (0.58 ± 0.08 mg∙g−1), TCC (0.14 ± 0.01 mg∙g−1), and β-carotene (0.94 ± 0.18 mg∙g−1) values. The antioxidant activity and FRAP assay were highest in P. oleracea (0.91 ± 0.09 mg∙g−1); the DPPH assay for P. pellucida was highest (IC50 = 7 µg∙mL−1). The amount of K was highest in P. oleracea (55.470 ± 0.481 g∙kg−1). The amount of Mn was highest in P. pellucida (0.251 ± 0.002 g∙kg−1). The individual underutilized vegetables may be able to supply some antioxidant compounds and mineral contents for the human diet.